The Existence of the Statement of the Companions (Fatwā Ṣaḥāba) and its Ḥujjah in Islamic Legal Thoughts - Hamid Pongoliu (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
Fatwā ṣahāba can be used as ḥujjah (proof) even though the ulama (scholars) have different opinions regarding its validity. The ulama categorize the Companions’ fatwā as one of the sources of law decision which is still being disputed about the validity. It is different from the Qur'an, Sunnah, Ijmā’, and Qiyās that have been agreed by the most of the scholars as a source of Islamic law. The Companions’ fatwā has an influence on the development of Islamic law thought which can be substantially equated like a fiqh, because it is the result of istinbāṭ (efforts to extract the ẓannī (speculative) sharia law from original sources through the mobilization of all natural reasoning abilities) and the results of the Companions ra'y (establish a law of contemporary problems that have not been found in the Qur’an and hadith) which have been codified according to the particular mazhab. Therefore, the Companions fatwā is the result of the ijtihad of the Companions as ulama of the previous generation and became the ḥujjah of the ulama until today who have colored Islamic law thought, such as fatwā of Abū Bakr, Umar, ‘Uthmān, ‘Alī, ‘Abdullāh Ibn ‘Abbās, ‘Abdullāh Ibn Mas'ūd and other Companions. At least the fatwā ṣaḥaba can be used as ḥujjah in istinbāṭ of islamic law when new problems arise, and no proposition is found in the Qur'an and hadith.